How Technology Information Advancement Mediates The Effect of Taxpayer Perception Toward Digitalization in Personal Tax Payer Filing - Muhammad Yusuf; Ahmad Hidayat Sutawidjaya; Gunawan Witjaksono; Imelda Oktaviani (Universitas Mercu Buana, 2023)
Taxes are a source of state income as much as the use of which is intended to improve the welfare of the community through the development and improvement of public facilities. Tax revenue comes from contributions generated from the community and for the community as well, this is because the results of the tax revenue are used for general financing rather than all government financing, even one of the benchmarks for the success or failure of a country's economyObjectives: This study aims to examine the factors that influence the use of e-Filing for individual taxpayers by using information technology readiness as an intervening variable.Methodology: The analysis method used a structural equation modeling (SEM) which is processed by using Smart PLS.Finding: The study's results indicate the following: Satisfaction perception has a positive impact on e-Filing adoption, whereas Perceptions of convenience, security, and confidentiality do not influence e-Filing usage. Additionally, Satisfaction perception does not affect information technology readiness, whereas Perceptions of convenience, security, and confidentiality have a positive effect on technology readiness. Furthermore, Satisfaction perception, along with security and confidentiality, positively impacts e-Filing utilization when mediated by technology information readiness. However, the perception of convenience does not affect e-Filing usage when technology readiness serves as an intermediary factor.Conclusion: Information technology readiness exerts a substantial influence on e-Filing utilization, signifying that higher information technology readiness leads to increased e-Filing adoption by taxpayers.